2019
DOI: 10.1186/s12889-019-7496-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated risk factors of peripheral artery disease in virologically suppressed HIV-infected individuals on antiretroviral therapy in Kwara state, Nigeria: a cross sectional study

Abstract: Background The association between HIV and cardiovascular disease (CVD) has been reported in several studies. However, there is paucity of information on the prevalence of subclinical disease as well as its associated risk factors in sub-Saharan African population. The aim of this study was to determine the prevalence and associated risk factors of peripheral artery disease (PAD) among virologically suppressed HIV-infected participants in Kwara State, Nigeria. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
0
8
0
5
Order By: Relevance
“…In a cross-sectional hospital-based study in black Africans, the LEAD prevalence was estimated at 6.9% 14 . A recent Nigerian study reported no difference of LEAD prevalence between virologically-suppressed individuals and controls 19 . Both studies defined LEAD as an ABI < 0.9 and had methodologic bias.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a cross-sectional hospital-based study in black Africans, the LEAD prevalence was estimated at 6.9% 14 . A recent Nigerian study reported no difference of LEAD prevalence between virologically-suppressed individuals and controls 19 . Both studies defined LEAD as an ABI < 0.9 and had methodologic bias.…”
Section: Discussionmentioning
confidence: 91%
“…Available data are issued from studies in hospitalized patients 13 , 14 , urban population 15 or age limited populations, using heterogenous definition of LEAD 14 , 16 or focusing on specific clinical LEAD stages 17 . Results are controversial 18 , 19 as study populations are not comparable. None of the studies reported any precise, accurate correlation between clinical stages of HIV disease and the prevalence of LEAD in African HIV population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in South Africa corroborate the ndings that HIV/AIDS-affected and infected youth face multiple deprivations of poverty [75,76], and food insecurity [77], which are commonly cited challenges for adolescents receiving HIV treatment and care in SSA. This is concerning because socioeconomic factors impact adherence to ART and retention in HIV care, which has implications for viral suppression and chronic disease pathways [78,79]. Addressing this challenge requires a multi-sectoral approach for NCD prevention with appropriate social protection systems to meet the needs of AYLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants required to show statistical significance is based on previously published studies in which vascular function was assessed in HIV patients [ 50 ]. An error probability (α) of 0.05, and power (1 − β) of 0.80 and an average effect size (d) of 0.5 were used to calculate the sample size (n = 64 persons).…”
Section: Methodsmentioning
confidence: 99%